Leucemia mieloide aguda. Reporte de un caso - González D., María S.; Caraballo G., Arley J. (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary Acute myeloid leukemia is a disease that affects one of the non-lymphoid cell lines from the bone marrow. This is a clinical case on a two year old, female, spayed, vaccinated poodle, previously diagnosed with Erlichia canis and treated with doxycycline and steroids. The poodle was taken to the Veterinary and Animal Sciences Centre of CES University (Medellin, Colombia), after suffering from vomiting, fever and severe weakness. Examinations included serial hemograms, coprological examinations, blood chemistry and serology test (ELISA) for Erlichia canis (found to be negative twice). A bone marrow aspiration was suggested because of suspicion of myelodysplasia. Subsequently, the poodle was euthanized with the owners consent and a bone marrow aspiration was performed. Results indicated acute myeloid leukemia. The objective of this article is to document this case due to its clinical importance and rare occurance.